Mitigating Polysulfide Shuttling in Li-S Battery - Li, Mengliu (KAUST Research Repository, 2019)
The energy source shortage has become a severe issue, and solving the problem with renewable and sustainable energy is the primary trend. Among the new generation energy storage, lithium-sulfur (Li-S) battery stands out for its low cost, high theoretical capacity (1,675 mAh g-1), and environmentally friendly properties. Intensive researches have been focusing on this system and significant improvement has been achieved. However, several problems still need to be resolved for its practical application, especially for the “shuttle effect” issue coming from the dissolved intermediate polysulfides, which could cause rapid capacity decay and low Coulombic efficiency (CE). Several methods are proposed to eliminate this issue, including using interlayers, modifying separators, and protecting the lithium anode.

A carbon interlayer is first introduced to compare the function of the graphene and carbon nanotubes (CNTs), while the CNTs performs better with its higher conductivity and 3D network structure. The following study is conducted based on this finding.

A more efficient method is to modify the separator with functional materials. 1) The dissolved polysulfide (Sn2-) could be repelled by electrostatic forces. With the Poly (styrene sulfonate) (PSS), the separator could function as an anion barrier to the intermediate polysulfides. 2D ultra-thin zinc benzimidazolate coordination polymer has the OH- functional groups and works with the same mechanism. 2) A novel covalent organic framework (COF) has a relatively small pore size, which can block the polysulfide and restrain them at the cathode side. 3) Metal-organic framework (MOF) materials have the adjustable pore size and structure, which can absorb and trap polysulfides within their cavities. Moreover, the dense stacking of the MOF particles creates a physical blocking for the polysulfides, which efficiently suppresses the diffusion process.

Protection of the lithium surface directly with an artificial layer or a solid electrolyte interphase (SEI) can inhibit the polysulfide deposition and suppress the lithium dendrite. A polyvinylidene difluoride (PVDF) membrane is used as an artificial film on lithium anode, which could greatly enhance the battery cyclability and CE. Future work will be conducted based on this concept, especially building an artificial SEI.